Technology Strategy In Industrial Automation - Chong, Chee Keong (2002)
The Second Industrial Master Plan (Th1P2) had identified industrial automation as one of the key industry group to transform Malaysia's manufacturing sector into an internationally competitive sector. The utilization of automation helps to improve manufacturers' competitiveness in terms of quality and operating costs, thus shifting the whole value chain to a higher level especially through productivity growh.